Risk of infections in psoriasis: assessment and challenges in daily management. (2nd November 2021) - De Simone, Clara; Fargnoli, Maria Concetta; Amerio, Paolo; Bianchi, Luca; Esposito, Maria; Pirro, Federico; Potenza, Concetta; Ricceri, Federica; Rongioletti, Franco; Stingeni, Luca; Prignano, Francesca
ABSTRACT: Introduction: In daily practice management of psoriasis, evaluation of risk factors for infections is having a growing influence. Indeed, in psoriatic patients, risk of infections may be due to psoriasis itself, immunomodulatory therapy, and comorbidities that may increase this risk and patient hospitalization. Areas covered: Given the greater understanding of psoriasis pathogenesis and the increasing number of treatment options, it is particularly important to customize therapy according to each, single patient; psoriasis features and comorbidities are also essential to tailor treatment goals. Expert opinion: In this perspective, the current knowledge on the infectious risk in psoriatic patient, related to comorbidities, such as diabetes mellitus, cardiovascular disease, and chronic obstructive pulmonary, to 'special populations, ' to chronic infections, such as latent tuberculosis, chronic hepatitis B and C, and HIV, and to the most recent Covid-19 pandemic scenario, is reviewed and discussed in order to suggest the most appropriate approach and achieve the best available therapeutic option.